Assessment of thermal comfort variability in mechanically ventilated lecture hall and hostel room - Zainol, Mohd Haris (2018)
The main focus of this study is to determine thermal comfort parameters which are CO2 concentration, relative humidity and temperature. These three parameters were identiﬁed as the main parameters that have the strongest relationship to ensure thermal comfort for indoor spaces were obtained. Mechanically ventilated lecture hall and hostel room in UMK and USM were selected to be used in this study by utilizing five differences temperature (22°C to 26"C) for lecture halls and varying fan speed and windows conditions for hostel room. The lecture halls were air conditioning ventilated while the hostel rooms are ceiling fans ventilated. The data were analyzed using descriptive analysis, time series plot, box and whisker plot and thermal comfort compliances tools. Online CBE thermal comfort tool was used to determine thermal comfort compliances to ASHRAE 55 for every predetermined condition of the lecture halls and hostel rooms. The result demonstrated that CO2 concentration at lecture hall UMK and lecture hall USM. CO1 concentration at hostel room follow the typical trend as higher concentration in the morning but for lecture hall has showed the opposite trend. The temperatures for hostel room also show that hostel room at UMK is higher than hostel room at USM. The results suggested that the best condition for lecture hall is 26‘C and for hostel room suggest the window is closed and fan speed of 3.